The Structure, Energy, Confinement, and Enhancement of Hot Spots between Two Nanoparticles - Perassi, Eduardo Marcelo (2013)
Hot spots (HSs) between two nanoparticles (NPs) can be considered the canonical example of plasmonic coupling effects and are able to achieve huge enhancements of signals from molecules in fluorescence and Raman spectroscopy. In this work, it is found that these HSs between two NPs can be modeled as a superposition of sub-HSs that are located on the surface of each NP of the pair, a fact that can be important to describe plasmon coupling effects. The analyzed HSs are almost fully characterized by means of their energy, degree of localization, and mean enhancement, quantities that are able to give a measure of their performance. It is demonstrated that the interplay between the energy and degree of localization is what actually determines the enhancement in a general way, that is, HSs with similar energy could have a large/small enhancement depending on their degree of localization.